2012
DOI: 10.1002/hbm.22105
|View full text |Cite
|
Sign up to set email alerts
|

fMRI evidence of degeneration-induced neuropathic pain in diabetes: Enhanced limbic and striatal activations

Abstract: Persistent neuropathic pain due to peripheral nerve degeneration in diabetes is a stressful symptom; however, the underlying neural substrates remain elusive. This study attempted to explore neuroanatomical substrates of thermal hyperalgesia and burning pain in a diabetic cohort due to pathologically proven cutaneous nerve degeneration (the painful group). By applying noxious 44°C heat stimuli to the right foot to provoke neuropathic pain symptoms, brain activation patterns were compared with those of healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 77 publications
2
46
0
Order By: Relevance
“…Our previous studies documented the influences of skin nerve degeneration on central processing of pain, ie, the level of brain fMRI activation was abnormally augmented in patients with neuropathic pain. 76 Electrophysiologically, the reduction in the magnitude of pain-evoked brain responses paralleled the degree of skin denervation. 17 The present findings extended our previous work, linking the pathological evidence of skin nerve degeneration with imaging signatures of structural and functional disruptions in pain-related regions.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our previous studies documented the influences of skin nerve degeneration on central processing of pain, ie, the level of brain fMRI activation was abnormally augmented in patients with neuropathic pain. 76 Electrophysiologically, the reduction in the magnitude of pain-evoked brain responses paralleled the degree of skin denervation. 17 The present findings extended our previous work, linking the pathological evidence of skin nerve degeneration with imaging signatures of structural and functional disruptions in pain-related regions.…”
Section: Discussionmentioning
confidence: 96%
“…However, it may be less effective to induce brain activations in patients without thermal hyperalgesia. 76 In this study, only 6 of the 19 patients had thermal hyperalgesia and 4 patients had mechanical allodynia only. As such, applying both mechanical (eg, brush) and thermal (heat and cold) stimulations in fMRI experiments may better detect functional brain responses in these patients with pure mechanical allodynia and facilitate the comparisons of modality-specific differences in fMRI activation patterns.…”
Section: Limitationsmentioning
confidence: 95%
See 2 more Smart Citations
“…These data indicate that there are some definitive alterations in the pain-processing matrix activation pattern in patients with painful neuropathy. 35 Another preliminary study using MRI spectroscopy reported the shift of excitatory-inhibition neurotransmitter balance in favor of excitatory glutamate in the posterior insula of diabetic patients with symptomatic neuropathy. 36 In summary, central manifestations seem to be associated with peripheral and autonomic neuropathy in diabetic patients.…”
mentioning
confidence: 99%